Markov Chain: An analysis of the precipitation levels in the Metropolitan Region of Recife-PE (Research, Society and Development, 2023)
This study presents an analysis of the precipitation index at six experimental stations operated by the Pernambuco Water and Climate Agency (APAC) to monitor the behavior of this index in selected municipalities of the metropolitan region of Recife, Pernambuco: Jaboatão dos Guararapes, Olinda, Várzea/Recife, Lamepe ITEP/Recife, Jaboatão dos Guararapes - TIP, and Camaragibe. Daily precipitation data were collected between 1960 and 2020. The following states were identified for use in the Markov chain: no rain, light rain, light to moderate rain, moderate rain, moderate to heavy rain, and heavy rain. Additionally, the 180-day moving window method was applied. The transition probability matrix of the Markov chain for the states mentioned above was obtained. This information is essential for estimating the probability of adverse events in which heavy rains can impact the lives of thousands of inhabitants in the Metropolitan Region of Recife (RMR). Future work can utilize this study's estimated transition probability matrix to simulate rainfall scenarios and assess potential risks of flooding and landslides.